Effects of annealing temperature on the structure, morphology, and photocatalytic properties of SnO2/rGO nanocomposites. (19th October 2020) - Tuan, Pham Van; Hieu, Le Trung; Hoang, Chu Manh; Tuong, Hoang Ba; Tan, Vu Thi; Hoa, Tran Thi Quynh; Sang, Nguyen Xuan; Khiem, Tran Ngoc
Abstract: Water pollution abatement is a problem in today's society that requires urgent attention. Moreover, photocatalysts are an effective method to treat environmental pollution, and SnO2 /reduced graphene oxide composite photocatalysts have been extensively studied in recent years. The synthesis parameters for these photocatalysts significantly affect their morphologies, structures, and properties. In this study, we investigated the effects of annealing temperatures on the properties of SnO2 /reduced graphene oxide nanocomposites, which were hydrothermally fabricated at 180 °C for 24 h and annealed at 200 °C–800 °C. The structural characteristics of the fabricated nanocomposites were studied via x-ray diffraction, field emission scanning electron microscopy, and Raman scattering analyses. The observed results indicated that increasing the annealing temperature from 200 °C to 800 °C increased the average SnO2 nanoparticle size from 4.60 nm to 9.27 nm; in addition, the Raman scattering peaks of the SnO2 increased, and those of the reduced graphene oxide significantly decreased as the annealing temperature was increased. Furthermore, the specific surface area of the samples decreased due to the increase in calcination temperature. The amount of reduced graphene oxide content in all the samples was measured using thermo-gravimetric analysis. The optical properties of the samples were studied using ltraviolet–visible absorption spectra, and their photocatalytic activity was evaluated by decomposing methylene blue under visible light using the samples as catalysts. In particular, the photocatalytic properties of nanocomposites decreased significantly with increasing annealing temperature. Among the samples, the photocatalytic activity of that annealed at 200 °C is most satisfactory as it has the smallest particle size and the largest specific surface area. The results of our research could facilitate the production of efficient catalysts with suitable properties.